2023
DOI: 10.1007/s00431-023-04825-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidental hypertransaminasemia in children—a stepwise approach in primary care

Abstract: Children with elevated liver enzymes are occasionally discovered through laboratory work-up from different clinical scenarios. Although the majority will have transient and/or benign conditions, a subgroup will have underlying liver disorders. The differential diagnosis is broad and therefore, a systematic approach is of utmost importance. In this article, we reviewed the most recent and relevant literature to provide a comprehensive overview of the main disease processes that cause hypertransaminasemia in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Our follow-up extended up to 3 years of life, and there was no indication to further investigations on liver function in any of the children [ 1 ]. A recent review suggested to conclude follow-up of an asymptomatic patient with normal physical examination and normal values of liver function tests in the presence of two consecutive normal tests 1 month apart [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our follow-up extended up to 3 years of life, and there was no indication to further investigations on liver function in any of the children [ 1 ]. A recent review suggested to conclude follow-up of an asymptomatic patient with normal physical examination and normal values of liver function tests in the presence of two consecutive normal tests 1 month apart [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kết quả nghiên cứu cũng tương tự như của Sanrni và cộng sự tại Thổ Nhĩ Kỳ cho thấy 194 (66,4%) là nam, (33,6%) là nữ, tuổi trung bình từ 6,5±5,4 tuổi [5]. Nghiên cứu của Costa (2023) [8], của Serdaroglu (2016) cũng tương tự [1].…”
Section: Bàn Luậnunclassified